Pharmacological strategies in extracorporeal membrane oxygenation weaning failure: a call to action - Francisco J. González-Ruiz; Francisco M. Baranda-Tovar; Luis A. Baeza-Herrera; José D. Utrilla-Álvarez; Ricardo E. Quirázco-Cordova; Gustavo Rojas-Velasco (Emergency and Critical Care Medicine)
Abstract. Extracorporeal membrane oxygenation has emerged as a viable alternative for stabilizing and improving critically ill patients in acute cardiovascular diseases. However, the weaning stage has been associated with a high morbidity and mortality rate. This makes searching for strategies that reduce failure in this final process necessary. Implementing a new approach must be tried and included in our protocols, seeking the patient’s well-being at all times. In this article, the authors discuss their point of view regarding potential pharmacological alternatives and the mechanism of action involved, which could decrease the mortality associated with this therapeutic.